Relevansi Pelaksanaan Masa ‘iddah terhadap Perkembangan Teknologi Medis Modern - Nawfal Hafiz Hasibuan; Iwan Nasution (Aksioreligia, 2026)
Advances in modern medical technology, which enable rapid and accurate detection of pregnancy and uterine conditions, have raised questions regarding their implications for the legal rationale ('illah) underlying the waiting period (‘iddah) in Islamic law. This study analyzes the relevance of the implementation of the waiting period (‘iddah) in Islamic law in relation to the development of modern medical technology, particularly in determining the condition of a woman’s uterus after divorce. This research uses a normative legal method with a library research approach based on the Qur’an, Hadith, tafsir, and fiqh literature. The findings show that ‘iddah aims to ensure womb purity, preserve lineage (nasab), and contains religious and social dimensions. Although modern medical technology can detect pregnancy quickly and accurately, it does not remove the obligation of ‘iddah due to its broader objectives in protecting lineage and maintaining Islamic family order. Thus, the observance of the ‘iddah period remains relevant in the modern era, and medical technology serves only as a supporting tool to strengthen certainty, rather than as a substitute for the obligation of ‘iddah.